1978
DOI: 10.1111/j.1478-4408.1978.tb03398.x
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Azo Compounds by Aeromonas hydrophila var. 24B

Abstract: A bacterium which has the ability to degrade azo dyes has been isolated from a polluted environment and identified as Aeromonas hydrophilia. The specificity of azo dyes to the bacterium was examined. p‐Acetamidoazobenzene, p‐aminoazobenzene, acetanilide, aniline and p‐phenylenediamine, which are produced as metabolites, were also isolated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

1990
1990
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(6 citation statements)
references
References 7 publications
0
4
0
2
Order By: Relevance
“…Most of the bacterial isolates from KTM were previously reported to be used in the degradation of dyes and related products [57][58][59][60][61][62][63]. Bacterial isolates sequentially adapted against higher concentration of four different dyes (Ar 151, Or II, Sb and Db K 2 RL) on solid medium exhibited varying MRLs ranging from 50 to 750 mg l −1 .…”
Section: Discussionmentioning
confidence: 99%
“…Most of the bacterial isolates from KTM were previously reported to be used in the degradation of dyes and related products [57][58][59][60][61][62][63]. Bacterial isolates sequentially adapted against higher concentration of four different dyes (Ar 151, Or II, Sb and Db K 2 RL) on solid medium exhibited varying MRLs ranging from 50 to 750 mg l −1 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that Aeromonas sp. could degrade azo dyes under either anaerobic or aerobic conditions (Du et al, 2015;Idaka et al, 2008;Shah, 2014). However, A. jandaei strain SCS5 could decolorize and degrade MR under both anaerobic and aerobic conditions suggesting that A. jandaei strain SCS5 would have high potential in the removal of azo dye MR.…”
Section: Decolorization Of Mr By Strain Scs5mentioning
confidence: 91%
“…The result of the study also supports the findings of this study. Linear relationships amongst these parameters were observed [7,8,9]. Most of these parameters are found to exceed beyond permissible limit and warrants treatment.…”
Section: Resultsmentioning
confidence: 99%